Surgical tactics of mediastinal bronchogenic cysts. A rare complication – cystobronchial fistula - S. A. Plaksin; A. A. Gorodilov (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to retrospectively study the results of treatment of mediastinal bronchogenic cysts (MBC), to present a case of the formation of a cystobronchial fistula after a transbronchial cyst puncture.METHODS AND MATERIALS. MBC were diagnosed in 11 (20 %) of 55 patients with various mediastinal cysts. The diagnosis was confirmed by computed tomography data, in one case by a transbronchial puncture. All patients were operated on.RESULTS. MBC was asymptomatic in 8 cases (72.7 %). Neoplasm in the mediastinum was detected during fluorographic examination in 5 patients, with CT in 6 cases. The dimensions of the cysts according to CT data were 45.5±15.2mm and 39.3±17.5mm, respectively. MRI was performed in two patients due to comorbid pathology of the spine. A 60-year-old patient underwent a transbronchial biopsy with biopsy forceps for diagnostic aim, as a result of which the cyst cavity was opened, infected, and a cystobronchial fistula with a diameter of 2 mm was formed with constant coughing up the purulent contents of the cyst. After anti-inflammatory, antibacterial therapy, after a month and a half, the cyst was removed by thoracotomy due to a pronounced periproccess. Video-assisted thoracoscopic cystectomy was performed for 9 patients. One patient was underwent conversion to thoracotomy due to the adhesive process after a previously performed lobectomy. Exudative pleurisy developed from postoperative complications in one case.CONCLUSION. The main method of diagnosing MBC is computed tomography. The ultrasound-guided transbronchial needle puncture of a cyst can be used to clarify the diagnosis under antibiotic prophylaxis, but can lead to infection of the cyst. Thoracoscopic excision of MBC should be considered the first-line therapeutic option due to the risk of complications and the presence of clinical manifestations.